The Rise of Social Media and the Fall in Mental Wellbeing among Young Australians - Andrew Leigh; Stephen Robson (Institute of Labor Economics (IZA), 2024)
Using multiple sources, we document a substantial worsening in the mental wellbeing of Australians aged 15-24, as measured by surveys, self-harm hospitalisations and suicide deaths. The shift began around 2007-2010 and is worse for young women than for young men. While several factors could be to blame, we present six pieces of evidence suggesting that smartphones and social media may have played a causal role in damaging the mental health of young Australians.
Keywords: D91; I12; L82; 330; mental health; technology; smartphones; social media